OPTIMIZATION OF SEX PHEROMONE DOSE AND TRAP DENSITY FOR MATING DISRUPTION OF CHILO SUPPRESSALIS (LEPIDOPTERA; PYRILADAE) - Abdul Waheed Solangi; Sajjad Ali Khuhro; Mehar Ul Nissa Rais (Journal of Animal and Plant Sciences, 2024)
The rice stem borer, Chilo suppressalis (Walker) is an oligophagous pest that mainly feeds on rice and currently is largely controlled through chemicals, leading to several ecological problems and often low control efficiency due to the larval feeding habits. Therefore, the alternative and eco-friendly control strategies is needed to manage this noxious insect pests, applications of trapping devices specifically sex pheromone traps are one of the most substitute control methods to monitoring and control moths by killing or mating disruption on large scale. The aim of the current study was to optimize the appropriate pheromone dose, trap density and trap placement height for mating disruption of C. suppressalis. During first year (2021), a mixture of two pheromones (Z11-16: Ald and Z9-16: Ald) in equal ratio (50:50) were applied at different doses (50, 100, 200, 300 and 500µg/20µL), with various trap heights (3, 4.5 and 6 feet) and compared with insecticide (fipronil G 0.2% 15 kg/ha). Results revealed that, 200 and 300µg/20µL caught significantly maximum (119.63±15.86) moths of C. suppressalis and resulted in lowest (4.96%) damage (white ear and dead hearts) as compared to other doses and treatments. The second year´s trial was designed to optimize the trap density in which 8, 12, 18 and 25 traps/ha were tested with a median dosage 250µg/20µl, based on first year’s results. It exhibited that 18 traps/ha captured maximum number (121.95±19.77) moths and reduced the damage symptoms significantly followed by other 25, 12 and 8 traps/ha with significant difference (P ≤0.001). Moreover, results of best treatment (appropriate sex pheromone dosage, trap placement height and trap density/ha) revealed highest (3:52) cost benefit ratio with minimum (7.90 $) expenditure also highest yield 7400 kg/ha was recorded as compared to other treatments. Therefore, installation of 18 traps/ha at 4.5 feet height with a dose of 250µg/20µL can manage C. suppressalis in rice-growing areas and consequently reduce management cost as compared to the insecticides. Thus, it is recommended as an important component for the eco-friendly management of rice stem borer to ensure food security.
Keywords: Chilo suppressalis; Pheromone dosage; Trap density; Trap height and mating disruption